Locating delaminations in laminated composite beams using nonlinear guided waves. (15th January 2017) - Soleimanpour, Reza; Ng, Ching-Tai
Highlights: Detect and locate delamination in laminated composite beams using nonlinear guided. Use of generation of higher harmonic guided wave due to clapping to detect and locate delamination. A baseline-free delamination localization technique using a network of transducers is proposed. Continuous Gabor wavelet transform is used to accurately determine the arrive time of higher harmonic guided wave. Comprehensive numerical and experimental case studies are provided. Abstract: This paper proposes a new method for detecting and locating delaminations in laminated composite beams using nonlinear guided wave. It is shown that when incident wave interacts at the delamination, the nonlinear effect of wave interaction with contact interfaces at the delamination generates higher harmonic guided waves due to contact acoustic nonlinearity (CAN). The proposed method employs a transducer network to detect and locate the delamination using the higher harmonic guided waves. A sequential scan is used to inspect the laminated composite beams by actuating the fundamental anti-symmetric mode (A0 ) of guided wave at one of the transducers while the rest of the transducers are used for measuring the impinging waves. A series of numerical case studies are performed using three-dimensional explicit finite element simulations, which consider different delamination locations, lengths and through-thickness locations. Experimental case studies are carried out to further validate and demonstrate the capability of the proposed method. The results show that the proposed method is able to accurately detect and locate the delamination in the laminated composite beams using the higher harmonic guided waves. One of the advantages of the proposed method is that it does not rely on baseline data to detect and locate the delamination, and hence, it has less influence by varying operational and environmental conditions.